Thomas E. Starzl, M.D., Ph.D—the Sui Generis Medical Pioneer and Mentor - Fung, John J.; Remzi, Merit (Frontiers in Transplantation, 2025)
As the “Father of Modern Transplantation”, Dr. Starzl pioneered every aspect of organ transplantation: immunosuppression, organ procurement and preservation, tissue matching, surgical transplant technology, and the operational management of the transplant team. His work paved the way for heart, lung, pancreas, intestinal, liver, and kidney transplantation and opened doors to understanding immune regulation of a number of acquired and inherited disorders. Dr. Starzl’s contributions to the scientific literature, in a span of 60 years, are nothing short of remarkable—2,872 publications placing him at the top of scientific citations according to the Institute of Scientific Information. Dr. Starzl was a man of unique vision, enthusiasm, and persistence; many of his ideas were considered revolutionary and radical—stimulating opposition and criticism. He called upon an inner strength, likely entrenched from his small-town upbringing, to persist in spite of adversity and promote social and medical acceptance of transplantation. Through his tireless efforts he educated scientists, other professionals, and the public. He was involved in all of the controversies of organ donation, from the use of non-heart beating donors, to living donors, to brain dead donor and to xenotransplantation (animal-to-human transplantation).